The influence of workplace environment and conflicts toward bank employees’ performance in Malaysia / Juliana Mohamed Abdul Kadir, Azila Jaini, Osveh Esmaeelinezhad, Siti Nurfakhira Mohd Zahidi and Nor Balkish Zakaria - Mohamed Abdul Kadir, Juliana; Jaini, Azila; Esmaeelinezhad, Osveh; Mohd Zahidi, Siti Nurfakhira; Zakaria, Nor Balkish (UiTM Cawangan Johor, 2024)
This paper attempts to determine the potential influence of physical workplace, psychosocial workplace, work-family conflicts, and work-extracurricular conflicts on the performance of bank employees. The research employed a quantitative method with the use of questionnaire as an instrument in data collection. The convenience sampling technique was adapted and the present study gathered 190 usable responses across 19 different banks located in Kuala Lumpur, Malaysia. Results reveal that the psychosocial workplace was positively affects staff performance. This implies that factors such as interpersonal connections, job satisfaction, organizational culture, and work-related stress levels can potentially wield substantial determinants of how effectively bank employees perform in their responsibilities. The study shed light on the employees' priorities that play a greater influence in enhancing employee performance than addressing physical challenges or the conflicts arising from the interplay between work and personal life. By highlighting the significance of the elements, the study calls for organizations to prioritize creating a positive and supportive psychosocial workplace for their employees. Future research could build upon these findings by considering additional variables, and exploring the applicability of the results across various industries and cultural contexts. This study provides insight into improving employees' performance in bank sectors. Supportive behaviours of supervisors have an important impact on employees ' performance and this research confirms the importance of creating a supportive work environment within the bank industry. Keywords: Banking Industry, Psychosocial Workplace, Physical Workplace, Work-Extracurricular Conflict, Work-Family Conflict